Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1902/jop.2010.090592
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Topography and Porosity of an Absorbable Barrier Membrane Impacts Soft Tissue Response in Guided Bone Regeneration

Abstract: The surface topographies engineered on different sides of the barrier promote differential soft tissue responses leading, however, to similar amounts of enhanced bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
(137 reference statements)
0
28
0
Order By: Relevance
“…Interspace was also created between the two layers of this membrane to facilitate tissue integration. In fact, the design and the architecture of the polymeric membranes are suggested to be important factors for determining their bioresorbability and osteopromotive effect in vivo .…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspace was also created between the two layers of this membrane to facilitate tissue integration. In fact, the design and the architecture of the polymeric membranes are suggested to be important factors for determining their bioresorbability and osteopromotive effect in vivo .…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
“…Interspace was also created between the two layers of this membrane to facilitate tissue integration. In fact, the design and the architecture of the polymeric membranes are suggested to be important factors for determining their bioresorbability and osteopromotive effect in vivo (179,184). The membranes described above differ not only with respect to their architecture but also in relation to thickness, which may influence their mechanical and spacemaintaining properties during implantation.…”
Section: Membrane Architecture and Thicknessmentioning
confidence: 99%
“…A multilayer scaffold has been suggested to achieve suitable mechanical properties and porosity and mimic the structure of cancellous and cortical bone [82]. In addition to the porosity, the tri-dimensional topography of the membrane with interconnecting pores and channels is also important, as it can alter the cell occlusion properties and the biologic response of different cell types to the membrane [83]. …”
Section: Introductionmentioning
confidence: 99%
“…Regenerative theraphy of furcation defect is challenging as well 18 . In guided tissue regeneration, resorbable and non-resorbable membranes are applied along with different bone materials 26,30 . Connective tissue was used in some researches as membrane for treatment of interproximal and furcation defects 3,5,9,13,15 , indicating controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of the periodontium within the furcation defect is one of the challenging aspects of periodontal therapy 18 . Initiation of osteogenesis and cementogenesis is a problem central to periodontal regeneration 24 .In guided tissue regeneration, resorbable and non-resorbable membranes are applied along with different bone materials in order to maintain space in bony defects and furcation 6,8,26,28,30 . One study showed that some genes are differentially expressed in membrane barrier-led periodontal healing compared with flap surgery alone, and this may account for the clinical outcome achieved by guided tissue regeneration 16 .…”
Section: Introductionmentioning
confidence: 99%